Deinococcus radiodurans Toxin–Antitoxin MazEF-dr Mediates Cell Death in Response to DNA Damage Stress - Li, Tao; Weng, Yulan; Ma, Xiaoqiong; Tian, Bing; Dai, Shang; Jin, Ye; Liu, Mengjia; Li, Jiulong; Yu, Jiangliu; Hua, Yuejin (Frontiers in Microbiology, 2017)
Here we identified a functional MazEF-dr system in the exceptionally stress-resistant bacterium D. radiodurans. We showed that overexpression of the toxin MazF-dr inhibited the growth of Escherichia coli. The toxic effect of MazF-dr was due to its sequence-specific endoribonuclease activity on RNAs containing a consensus 5’ACA3’, and it could be neutralized by MazE-dr. The MazF-dr showed a special cleavage preference for the nucleotide present before the ACA sequence with the order by U>A>G>C. MazEF-dr mediated the death of D. radiodurans cells under sub-lethal dose of stresses. The characteristics of programmed cell death (PCD) including membrane blebbing, loss of membrane integrity and cytoplasm condensation occurred in a fraction of the wild-type population at sub-lethal concentration of the DNA damaging agent mitomycin C (MMC); however, a MazEF-dr mutation relieved the cell death, suggesting that MazEF-dr mediated cell death through its endoribonuclease activity in response to DNA damage stress. The MazEF-dr-mediated cell death of a fraction of the population might serve as a survival strategy for the remaining population of D. radiodurans under DNA damage stress.